3D FE Analysis of Thermal Behavior of Billet in Rod and Wire Hot Continuous Rolling Process - YUAN, Si-yu; ZHANG, Li-wen; LIAO, Shu-lun; QI, Min; ZHEN, Yu; GUO, Shu-qi (Journal of iron and steel research, international, 2007)
An FE model was developed to study thermal behavior during the rod and wire hot continuous rolling process. The FE code MSC. Marc was used in the simulation using implicit static arithmetic. The whole rolling process of 30 passes was separated and simulated with several continuous 3D elastic-plastic FE models. A rigid pushing body and a data transfer technique were introduced into this model. The on-line experiments were conducted on 304 stainless steel and GCr15 steel hot continuous rolling process to prove the results of simulation by implicit static FEM. The results show that the temperature results of finite element simulations are in good agreement with experiments, which indicate that the FE model developed in this study is effective and efficient.